2016
DOI: 10.1093/mnras/stw1325
|View full text |Cite
|
Sign up to set email alerts
|

Determining the mid-plane conditions of circumstellar discs using gas and dust modelling: a study of HD 163296

Abstract: The mass of gas in protoplanetary discs is a quantity of great interest for assessing their planet formation potential. Disc gas masses are, however, traditionally inferred from measured dust masses by applying an assumed standard gas-to-dust ratio of g/d = 100. Furthermore, measuring gas masses based on CO observations has been hindered by the effects of CO freeze-out. Here we present a novel approach to study the mid-plane gas by combining C 18 O line modelling, CO snowline observations and the spectral ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 74 publications
(169 reference statements)
10
35
0
Order By: Relevance
“…If so, the implication is that ∆ g/d ≈ 20-50. This relative depletion of gas over dust is supported by the hydrostatic MCMax modelling of the SED and low-J 12 CO, 13 CO, and C 18 O lines by Boneberg et al (2016), whose best models had 9.2 < ∆ g/d < 18. It is also consistent with the inner disk value ∆ g/d ≈ 55, measured using accre- 3.…”
Section: Hd 163296mentioning
confidence: 73%
See 1 more Smart Citation
“…If so, the implication is that ∆ g/d ≈ 20-50. This relative depletion of gas over dust is supported by the hydrostatic MCMax modelling of the SED and low-J 12 CO, 13 CO, and C 18 O lines by Boneberg et al (2016), whose best models had 9.2 < ∆ g/d < 18. It is also consistent with the inner disk value ∆ g/d ≈ 55, measured using accre- 3.…”
Section: Hd 163296mentioning
confidence: 73%
“…Most previous estimates of the HD 163296 gas mass relied on low-J emission lines of CO isotopologs, and used a range of modelling approaches from generic model grids to tailored modelling with physical-chemical codes. Those M gas estimates range from 8×10 −3 to 5.8×10 −1 M (Isella et al 2007;Williams & Best 2014;Boneberg et al 2016;Miotello et al 2016;Williams & McPartland 2016;Powell et al 2019;Woitke et al 2019;Booth et al 2019). The mass obtained from the most optically thin isotopolog among these, 13 C 17 O, was 2.1 × 10 −1 M (Booth et al 2019).…”
Section: Hd 163296mentioning
confidence: 99%
“…In the absence of direct measurements of the radial flow of gas through discs, the accretion rate onto the star combined with the disc mass provide the most reasonable estimates. For example, Boneberg et al (2016) found that an effective α ∼ 0.1 was required to match the accretion rate of HD 163296, while the turbulent mixing in the vertical direction was lower. Furthermore, based on the surface density profile and accretion rate Clarke et al (2018) derive α ∼ 0.01 for CI Tau.…”
Section: Physical Parametersmentioning
confidence: 99%
“…Evidence for enhanced dust to gas mass ratios have been claimed in a number of systems, though currently these are typically all in a higher mass regime (e.g. Meeus & et al 2010;Isella et al 2012;Muto et al 2015;Pinte et al 2016;Boneberg et al 2016;Ansdell et al 2016;Long et al 2017). Our models suggest that external photoevaporation significantly alters the global dust-to-gas mass ratio of protoplanetary discs by more effectively stripping the gas than the dust, at least about low mass stars like Trappist-1.…”
Section: G0mentioning
confidence: 99%